(3aVd GdbhS heG jaOdQGejg ef GdKhGHs - (3eLghds
(3ChdgG (B:s
(3ChdgG(B: (3cJGH aVd GdbhS GdYQHjI, MOKfG YHO Gddg Hf GdMSjf GdQbj, MOKfG GdbGVj GHf GdCTjH, bGd(B: (3MOKfG GHf CHj GdOfjGs
(3BNQgG (B:s
(3BNQgG(B: (3hGUd GdejhfQL GdeYJUQ CHdZ aj GdaYd ef GdjGHS GdefJbY HGdeGA hEf SbjJ ScjJfjf gQHJ GdhGMOI ef GdCNQi hGddg CYde(B. (3Je GdcJGHs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3GdJedcGJ h GdhbajGJ (B:s
(3Jedc HGSe(B: (3eUWai LhQfLj GdaQNGfj (B1140(3g`s
Keywords: (3GdeYGQa GdYGeIs